2016
DOI: 10.1038/srep23116
|View full text |Cite
|
Sign up to set email alerts
|

Functionally different α-synuclein inclusions yield insight into Parkinson’s disease pathology

Abstract: The formation of α-synuclein (α-S) amyloid aggregates, called Lewy bodies (LBs), is a hallmark of Parkinson’s disease (PD). The function of LBs in the disease process is however still unclear; they have been associated with both neuroprotection and toxicity. To obtain insight into this contradiction, we induced the formation of α-S inclusions, using three different induction methods in SH-SY5Y cells and rat-derived primary neuronal cells. Using confocal and STED microscopy we observed induction-dependent diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…This finding is consistent with the idea that different toxic αSyn strains are present contingent on the differing synucleinopathy clinical and pathologic states (32,33). Furthermore, the current data support the hypothesis that different conformations and/or posttranslational modifications can confer varying degrees of αSyn strain toxicity or infectivity, which may in turn drive the rate of disease progression (10,32,34,35). The potential differences between the discrete αSyn strains have yet to be clearly elucidated.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with the idea that different toxic αSyn strains are present contingent on the differing synucleinopathy clinical and pathologic states (32,33). Furthermore, the current data support the hypothesis that different conformations and/or posttranslational modifications can confer varying degrees of αSyn strain toxicity or infectivity, which may in turn drive the rate of disease progression (10,32,34,35). The potential differences between the discrete αSyn strains have yet to be clearly elucidated.…”
Section: Discussionsupporting
confidence: 89%
“…The consensus emerged that oligomers, generated on or off the pathway to amyloid formation or resulting from fibril degradation, are primary players in protein-misfolding toxicity (49)(50)(51)(52). The involvement of pα-syn in PD pathology was recognized exactly two decades ago (10), and numerous studies have examined the morphology and localization of α-syn aggregates (14,53). Recently, the concept has emerged of the existence of different "strains" of α-syn aggregates by analogy to prions, which are aggregates of misfolded prion protein (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increased knowledge in this field, our understanding of the roles of different α-syn aggregates for the propagation of pathology in Lewy body disorders remains incomplete. However, it has been shown that α-syn aggregates can cause cellular toxicity depending on intracellular locations [21], and evidence suggests detrimental effects on both mitochondrial [22] and lysosomal [19] functions, as well as autophagy [23] and calcium homoeostasis [24]. …”
Section: Introductionmentioning
confidence: 99%